Using Bioinformatics Application to Predict and Detect Single ‎Nucleotide Polymorphism (SNP) in Eukaryotic Organism : Using Bioinformatics Application to Predict and Detect (SNP) - Hassan, Hala; Muhammed, Hisham (Iraqi Journal of Aquaculture, 2026)
The rapid development of bioinformatics has made data analysis essential for understanding biological processes requiring advanced molecular techniques for detection and prediction based on specific artificial intelligent program and algorithm such as ANN (Artificial Neural Network), The main objective of this research to predictive for rotifers (Brachionus plicatilis and Brachionus calyciflorus) depending on genetic data which including fifty samples from rotifers species collected from different area in Basrah city water. Fifty samples of the 18S rRNA gene products were subjected to PCR amplification and sequencer also applied artificial neural network program to predict and detect SNP, this study considered one of the very encouragement research for highly confirmed technique in different types of rotifers with short time and low cost application.